Analisis Korelasi Kesepian Emosional, Sensation Seeking, dan Kecenderungan Penggunaan Instagram pada Remaja - Ariqa, Rizki; Galugu, Nur Saqinah; Fahmi, Ainul (Universitas Muhammadiyah Metro, 2023)
This era of globalization is a digital era where almost everyone can use smartphones and the internet to make their daily lives easier. The era of digital development was also followed by the rapid development of information technology, one of information technology is social media. this research is a quantitative research with correlation research design. The population of this study were students of the Teaching and Education Faculty of Muhammadiyah University of Palopo. The sample in this study was 171 people who were selected using a purposive sampling technique with the criteria of having Instagram accounts and active Instagram users. The measuring instrument used in this research is the tendency to use Instagram by using the Del Bario scale, whereas sensation seeking uses the sensation-seeking scale form v, and loneliness is measured by using the UCLA Loneliness scale version 3. Data were analyzed using multiple linear regression analysis techniques with the assistance of SPSS 20 program for windows. The results of this study indicate that there is a relationship between emotional loneliness and the tendency to use Instagram (p value = 0.001 0.05) is in the weak category and the direction of positive correlation. Sensation seeking also has a relationship with the tendency to use Instagram (p value = 0.000 0.05) is in the weak category and the direction of a positive correlation, which means that the higher the level of emotional loneliness, the higher the tendency to use Instagram in adolescents, as well as sensation seeking, which means that the higher the level of sensation seeking, the higher the level of tendency to use Instagram in adolescents. Thus it can be concluded that the two variables, which are emotional loneliness (X1) and sensation seeking (X2) have a relationship with the tendency to use Instagram (Y).